Policy uncertainty and FDI: Evidence from national elections. Issue 4 (19th May 2019) - Chen, Kexin; Nie, He; Ge, Zhenyu
ABSTRACT: This paper examines the impact of policy uncertainty on FDI among 126 countries from 1996 to 2015. Using the timing of national elections as a proxy for policy uncertainty, we find that FDI drops significantly in election years, when policy uncertainty increases. The negative effect of policy uncertainty on FDI also depends on the degree of democratization and the political system. In democracies and countries with the Assembly elected president, the decline of FDI in election years is far more pronounced. Our results highlight the role of policy environment and institution in economic development.